Model Tests on a Triple Screw Icebreaker (M5) for the United States Coast Guard. Part I - Resistance and Propulsion Tests - Dix, P. J. (1967)
This report describes model tests on a new design Triple Screw Icebreaker to determine the propulsion characteristics. Details of the experiments were specified in the test programme and the work was carried out on behalf of the United States Coast Guard. See also Part 2, AD-861 591L.